Hubungan antara Motivasi Kerja dan Psychological Well- Pembentukan Superelevasi Jalan pada Pekerjaan Timbunan Ringan Mortar Busa Berdasarkan Setting Time - Halim Pelu; Budi Hartanto Susilo; Darmawan Pontan (Jurnal Syntax Admiration, 2024)
This study examines the relationship between work motivation and psychological well-being (PWB) in internship students in Jabodetabek. The Kampus Merdeka program policy provides opportunities for students to develop their skills and work experience. This study aims to identify how work motivation, both intrinsic and extrinsic, affects the psychological well-being of student interns. Using a predictive correlational approach, data were collected through questionnaires measuring the dimensions of work motivation and PWB. The results showed that intrinsic motivation has a significant positive impact on psychological well-being, while excessive extrinsic motivation can have a negative impact. The research emphasizes the importance of creating a supportive work environment to motivate student interns, improve their performance, and prepare them for the transition from academia to the world of work. The researcher obtained 103 respondents from various students in Jabodetabek. universities with 25.2% male and 74.8% female gender. This research data was processed using convenience sampling techniques, using the Multidimensional Work Motivation Scale (MWMS) questionnaire and Psychological Well Being (PWB) distribution this questionnaire through social media by using google form. The analysis of the data is known through the Kolmogorov Smirnov test obtained a figure of 0.200> 0.05 for both variables, it is concluded that the residual data is normally distributed.